A House of Prayer for All Peoples: Congregations Building Multiracial Community - Kujawa-Holbrook, Sheryl A. (Rowman & Littlefield Publishers, 2002)
Contrary to the oft-repeated truism, there are churches in America where Sunday is not the "most segregated day of the week," as Sheryl Kujawa-Holbrook convincingly demonstrates in her compelling exploration of congregations tackling racial justice issues. Yet the truism continues to haunt many congregations, and Kujawa-Holbrook reveals, through story and thoughtful analysis, what it means to create and live out multiracial community. Focusing on six congregations from different denominations, geographical regions, and settings, the author shows us the joys and struggles in their intentional pursuits of a more diverse and just community. The stories in A House of Prayer for All Peoples will inspire leaders to explore their congregation's history, study their community's demographics, and, most of all, search their souls for ways they can develop and celebrate the diversity in their midst. The book is capped by an extensive annotated resource list for readers who want to explore the topic further.